Total factor productivity growth and export-led strategies: Reviewing the cross-country evidence - Armando Castelar Pinheiro (Institute for Applied Economic Research (ipea), 2015)
In this paper we review, examine and comment the empirical li terature that relies on cross-country statistical analyses to show that export orientation has a positive and significant impact on total factor productivity growth. We comment the work reviewed along four lines. First, we address the question of properly identifying the degree of export bias of an economy and the ways by which exports and growth are related. Second, we consider the sensitivity of the results to sample and period selection. Third, we review the evidence with respect to the direct íon of causali ty between export and output growth. Finally, we extend the analysis beyond the single-equation cross-country regression model to see the relevance of specification problems. Our main conclusion is that, although adequate to search for stylized facts, the cross-country model is not the best way to examine the association between total factor productivity growth and trade orientation.
Keywords: 330